What should be done about rising unemployment in the OECD? - Bell, David N.F.; Blanchflower, David G. (Bonn, 2009)
"There is a growing belief that the recession has run its course and that the goods market has started a period of slow, but sustainable, recovery. Improvement in the labor market may take some time, but many believe that unemployment will return to its 2007 level in the medium term. In this paper, we argue that recovery is by no means guaranteed and that the consequences for unemployment may be worse than anticipated."